Cryptosporidiosis in puppies: clinical and epizootical characteristics - O. A. Dubova; D. V. Feshchenko; A. A. Dybovyi; V. V. Zakharin (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
Gastrointestinal diseases of puppies aged 2–6 months account for 62% of all pathologies of these animals registered in the clinic. The lifestyle of dogs is associated with close tactile contact with the environment. The presence of protozoa in the digestive tract causes the inclusion of its representatives in the pathological process, which leads to the complication of disorders that have arisen due to various etiological factors. The study aimed to determine the role of the ubiquitous protozoa Cryptosporidium spp. in the pathogenesis of digestive tract diseases in puppies. General clinical, laboratory tests of blood (haematological, biochemical), faeces (coprogram, parasitological), statistical processing were performed. It was found that protozoa were detected in 52 % of sick animals with digestive disorders. The protozoan fauna included Cryptosporidium spp. (100 %), Isospora spp. (29 %), Giardia lamblia (21 %). Animals with cryptosporidium were examined without associations. The manifestation of the disease was noted most often in puppies with weak immune system functions, especially in the age group of 4–5 months, which is associated with the period of tooth change and a decrease in the overall immunological reactivity of the body. Clinically, the disease is characterized by enteritis development with accompanying symptoms. A characteristic clinical sign that should guide further diagnostic search is watery diarrhoea with an unpleasant odour, foamy, mucus, sometimes blood streaks. Laboratory findings include hypoalbuminemia with a decrease in the albumin-globulin ratio, hyperbilirubinaemia due to conjugated bilirubin, hyperfermentation of indicator enzymes of the liver and pancreas, and uremia. Such indicators indicate concomitant insufficiency of the digestive glands – the liver and pancreas, and a general inflammatory reaction. In coprological diagnostics, the qualitative data of the coprogramme confirm the lesions of the small intestine, liver and pancreas. Examination of fecal smears stained by the Ziehl-Nielsen method revealed cryptosporidium oocysts. The average intensity of invasion was 786.4 ± 23.1 oocysts per gram of feces.